Síntese e estereoquímica de isoxazóis espiro-tetracíclicos trifluormetil substituídos - Ketzer, Alex (2017)
The present dissertation initially describes methodologies for the synthesis of five 3-(trifluoromethyl)-3,3a-dihydrospiro[chromeno[4,3-c]isoxazole-4,1'-cycloalkan]-3-ols (7) in 65 – 84 % yields, where the spirocarbocyclic portion is constituted by: cyclopentane, cyclohexane, cycloheptane, 4-methyl-cyclohexane or 4-tert-butyl-cyclohexane. The isoxazolines 7 where synthesized through cyclocondensation [3+2] employing 2,2,2-trifluoro-1-(4-methoxyspiro[chromene-2,1'-cyclopentan]-3-yl)ethan-1-one (6) as the 1,3dieletrophile [CCC], and hydroxylamine chloridrate as the 1,2-dinucleophile [NO] in the presence of NaHCO3 in 65 – 84 % yields. The stereochemistry involved in the isoxazolines (7) synthesis was discussed and elucidated using 1H, 13C, 19F NMR, HMQC, HMBC e NOESY 2-D-NMR and single crystal X-ray diffraction. In sequence the 3-(trifluoromethyl)-3,3a-dihydrospiro[chromeno[4,3-c]isoxazole-4,1'-cycloalkan]-3-ols (7) were dehydrated aiming to furnish a novel series of five 3-(trifluoromethyl)spiro[chromeno[4,3-c]isoxazole-4,1'-cycloalkanes] (8). The dehydration was successfully performed in benzene/thionyl chloride media in 76 – 95 % yields. In a next reaction step the isoxazolines (7) were derivativated with propargyl bromide through a NS2 reaction furnishing a novel heterocyclic series of five 3-(prop-2-yn-1-yloxy)-3-(trifluoromethyl)-3,3a-dihydrospiro[chromeno[4,3-c]isoxazole-4,1'-cycloalkanes] (10) in 71 – 84 % yields. Finally the isolated terminal alkynes were successfully employed in the construction of a series of five examples of 3-((1-benzyl-1H-1,2,3-triazol-4-yl)methoxy)-3-(trifluoromethyl)-3,3a-dihydrospiro[chromeno[4,3-c]isoxazole-4,1'-cycloalkanes] (12), in 36 – 84% yields. The methylene-bi-heterocyclic series (12), composed exclusively of 1,4-dissubstituted 1,2,3-triazoles, was obtained through a regoiselective 1,3 dipolar cycloaddition (Click Chemistry) catalyzed by copper iodide using terminal alkynes (10) and benzil Azide (NNN fragment).